High Active Co/Mg1-xCex3+O Catalyst: Effects of Metal-Support Promoter Interactions on CO2 Reforming of CH4 Reaction - Faris A. Jassim Al-Doghachi; Diyar M. A. Murad; Huda S. Al-Niaeem; Salam H. H. Al-Jaberi; Surahim Mohamad; Yun Hin Taufiq-Yap (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2021)
Co/Mg1−XCe3+XO (x = 0, 0.03, 0.07, 0.15; 1 wt% cobalt each) catalysts for the dry reforming of methane (DRM) reaction were prepared using the co-precipitation method with K2CO3 as precipitant. Characterization of the catalysts was achieved by X-ray diffraction (XRD), X-ray fluorescence spectroscopy (XRF), X-ray photoelectron spectroscopy (XPS), temperature programmed reduction (H2-TPR), Brunauer–Emmett–Teller (BET), transmission electron microscopy (TEM), and thermal gravimetric analysis (TGA). The role of several reactant and catalyst concentrations, and reaction temperatures (700–900 °C) on the catalytic performance of the DRM reaction was measured in a tubular fixed-bed reactor under atmospheric pressure at various CH4/CO2 concentration ratios (1:1 to 2:1). Using X-ray diffraction, a surface area of 19.2 m2.g−1 was exhibited by the Co/Mg0.85Ce3+0.15O catalyst and MgO phase (average crystallite size of 61.4 nm) was detected on the surface of the catalyst. H2 temperature programmed reaction revealed a reduction of CoO particles to metallic Co0 phase. The catalytic stability of the Co/Mg0.85Ce3+0.15O catalyst was achieved for 200 h on-stream at 900 °C for the 1:1 CH4:CO2 ratio with an H2/CO ratio of 1.0 and a CH4, CO2 conversions of 75% and 86%, respectively. In the present study, the conversion of CH4 was improved (75%–84%) when conducting the experiment at a lower flow of oxygen (1.25%). Finally, the deposition of carbon on the spent catalysts was analyzed using TEM and Temperature programmed oxidation-mass spectroscopy (TPO-MS) following 200 h under an oxygen stream. Better anti-coking activity of the reduced catalyst was observed by both, TEM, and TPO-MS analysis. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).